Error Analysis and Correction of Voltage Sag Measurement for Capacitor Voltage Transformer - Wen ZHOU; Jifeng LIANG; Yadong JIAO; Tiecheng LI; Yanqiao LU; Yong LIU (Zhongguo dianli)
Voltage sag is one of the most prominent power quality problems in modern power grid. When monitoring voltage sag in a large range of high-voltage systems, the adverse effects caused by capacitor voltage transformer (CVT) with energy storage elements must be considered. According to the structure of the CVT, the error of voltage sag measurement is deduced, and the internal and external factors influencing the error are identified. Then, a simulation model is built, and a study is made in detail on the influences and sensitivities of the initial phase angle of sag, residual voltage, CVT parameters and load on voltage sag duration, sag amplitude and phase jump. Finally, a virtual impedance compensation based method is proposed for CVT’s voltage sag measurement error correction, which eliminates the problem of measurement error diversity caused by voltage sag uncertainty. The simulation results show that the method is effective and provides a feasible correction scheme for the accurate measurement of voltage sag in the high-voltage system which widely adopts CVT.